Tunable Near-Infrared Luminescence in Tin Halide Perovskite Devices - Lai, May L; Tay, Timothy Y. S; Sadhanala, Aditya; Dutton, Siân E; Li, Guangru; Friend, Richard H; Tan, Zhi-Kuang (The journal of physical chemistry letters, 2016)
Infrared emitters are reasonably rare in solution-processed materials. Recently, research into hybrid organo-lead halide perovskite, originally popular in photovoltaics, − has gained traction in light-emitting diodes (LED) due to their low-cost solution processing and good performance. − The lead-based electroluminescent materials show strong colorful emission in the visible region, but lack emissive variants further in the infrared. The concerns with the toxicity of lead may, additionally, limit their wide-scale applications. Here, we demonstrate tunable near-infrared electroluminescence from a lead-free organo-tin halide perovskite, using an ITO/PEDOT:PSS/CH3NH3Sn(Br1–x I x )3/F8/Ca/Ag device architecture. In our tin iodide (CH3NH3SnI3) LEDs, we achieved a 945 nm near-infrared emission with a radiance of 3.4 W sr–1 m–2 and a maximum external quantum efficiency of 0.72%, comparable with earlier lead-based devices. Increasing the bromide content in these tin perovskite devices widens the semiconductor bandgap and leads to shorter wavelength emissions, tunable down to 667 nm. These near-infrared LEDs could find useful applications in a range of optical communication, sensing and medical device applications.